IMPLEMENTASI METODE DRILL DALAM MENINGKATKAN BACA TULIS AL-QUR’AN SISWA KELAS IV MI BUSTANUL IMAN PEGANDON KARANGDADAP KABUPATEN PEKALONGAN - Wulida, Khurrul Fikri; Nasokah, Nasokah; Amin Nugroho, Muhammad Yusuf (Fakultas Ilmu Tarbiyah dan Keguruan, Universitas Sains Al-Qur'an (UNSIQ) Jawa Tengah di Wonosobo, 2024)
The purpose of this research is to determine: 1) the concept of the drill method from the perspective of teachers at MI Bustanul Iman Pegandon, Karangdadap, Pekalongan Regency; 2) the application of the drill method in improving the ability to read and write the Qur'an among fourth-grade students at MI Bustanul Iman Pegandon, Karangdadap, Pekalongan Regency; 3) the supporting and inhibiting factors in the implementation of the drill method to enhance the reading and writing skills of the Qur'an among fourth-grade students at MI Bustanul Iman Pegandon, Karangdadap, Pekalongan Regency. This type of research uses qualitative methods. Data collection techniques involve interviews, observations, and documentation. Once the data is collected, it is analyzed using data analysis techniques, which include data collection, data reduction, presentation, and conclusions. Based on this research, it is concluded that: 1) The drill method from the perspective of the teachers at MI Bustanul Iman is largely the same, describing the method as a way of teaching through repetition of material so that students develop skills in the subjects being taught. 2) The implementation of the drill method in improving the ability to read and write the Qur'an among fourth-grade students at MI Bustanul Iman is carried out well and yields positive results. The drill method applied in the fourth grade consists of several steps: Preparation, Presentation of Material, Practice, Evaluation, and Reflection. The results achieved from using the drill method over one year of learning show that approximately 80% of the fourth-grade students improved in their ability to read and write the Qur'an. In Class IV A, out of 18 students, 15 showed improvement, while in Class IV B, about 10 out of 15 students improved. This improvement is observed in their pronunciation during Qur'an reading practice and in their writing, as they replicate what the teacher has written. 3) Supporting factors for the drill method in BTQ (Baca Tulis Qur'an) learning for fourth grade at MI Bustanul Iman include student and teacher enthusiasm, student capability, and supporting learning facilities. Meanwhile, the inhibiting factors for the drill method in enhancing the reading and writing skills of the Qur'an among fourth-grade students at MI Bustanul Iman include a lack of enthusiasm from students and teachers during learning, insufficient reading and writing ability in the Qur'an among students, and inadequate learning facilities.